ETIKA PRODUKSI ISLAMI: MASLAHAH DAN MAKSIMALISASI KEUNTUNGAN - Hardi, Eja Armaz (El-Jizya : Jurnal Ekonomi Islam, 2020)
This article explores the comparative concept of profit maximization and mas}lah}ah in the process of forming the final price in the production cycle. In conventional economics, profits can be formed through various market models faced by producers to achieve maximum profits. on the other hand, Islamic economics views that producer profits must contain Islamic values. This value is reflected in the production goals, which must contain mas}lah}ah and uphold the ethics and norms of consumers and producers. The ultimate goal of mas}lah}ah is a manifestation of maqasid sharia which is to achieve world happiness and the hereafter (fala<h}). In order to answer the anxiety above in the sections of this article discuss some topics related to profit maximization. In the first part of this article discussed the ethical issues of producers and their relation to religion. Then the theory of production, production goals, price theory, and profits, then all the discussion in this article will compare the Islamic perspective and conventional perspective in detail. At the end of this article see a review of Maqasid Sharia and mas}lah}ah of production. This article finds that production activities in the conventional and economic context of Islam must pass synergy in several aspects. In order to achieve the establishment of production theory, Islamic ethical values ​​must contribute to the maximization of profits in production activities. The concept of mas}lah}ah on the theory of Islamic production has values ​​which include: baraka; mas}lah}ah, and; fala<h}. Such values ​​must go hand in hand with conventional production theories.